The Escherichia coli motA flagellar gene as a potential integration site for large synthetic DNA - Yip, Chee-Hoo; Yarkoni, Orr; Juhas, Mario; Ajioka, James; Wan, Kiew-Lian; Sheila Nathan, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Escherichia coli is used as a chassis for many synthetic biology applications. However, the limitations of maintaining recombinant plasmids extra-chromosomally include increased metabolic burden to the host, constant selective pressure, variable plasmid copy number and plasmid instability that leads to curing. Hence, to overcome these limitations, DNA constructs are integrated into the bacterial chromosome to allow stable control of copy number and to reduce the metabolic burden towards the surrogate host. Non-essential E. coli flagellar genes have been proposed as potential chromosomal insertion target sites. In this study, we validated and compared the efficiency of two loci, namely motA and flgG, as target sites for synthetic biology applications. To enable this comparison, a dual reporter strain (DRS) that utilises two reporter proteins, EforRED and Venus, was developed as a test case. Initially, a yellow reporter plasmid k14.1_Venus was constructed and subsequently used as the plasmid backbone for the generation of two other plasmids, k14.1_eforRED and pcat_Venus, required to build the dual reporter strain. In the DRS, the eforRED gene was inserted into flgG whereas motA was disrupted by Venus. This mutant strain was defective in motility (p<0.001) but growth rate was unaffected. The fluorescence emitted by Venus was higher (p<0.05) compared to EforRED, suggesting that motA is the better chromosomal target locus compared to flgG. Hence, this study proposes the use of E. coli motA as the site for chromosomal insertion for future synthetic biology applications.